Development and Entrainment of the Fetal Clock in the Suprachiasmatic Nuclei: The Role of Glucocorticoids - Čečmanová, Vendula; Houdek, Pavel; Šuchmanová, Karolína; Sládek, Martin; Sumová, Alena (Journal of biological rhythms, 2019)
The adult circadian clock in the suprachiasmatic nucleus (SCN) of the hypothalamus is resilient to glucocorticoids (GCs). The fetal rodent SCN resembles that of the adult in its organization of GC-sensitive peripheral tissues. We tested the hypothesis that the fetal SCN clock is sensitive to changes in GC levels. Maternal GCs must pass through the placenta to reach the fetal SCN. We show that the maternal but not the fetal part of the placenta harbors the autonomous circadian clock, which is reset by dexamethasone (DEX) and rhythmically expresses Hsd11b2. The results suggest the presence of a mechanism for rhythmic GC passage through the placental barrier, which is adjusted according to actual GC levels. GC receptors are expressed rhythmically in the laser-dissected fetal SCN samples. We demonstrate that hypothalamic explants containing the SCN of the mPer2 Luc mouse prepared at embryonic day (E)15 spontaneously develop rhythmicity within several days of culture, with dynamics varying among fetuses from the same litter. Culturing these explants in media enriched with DEX accelerates the development. At E17, treatment of the explants with DEX induces phase advances and phase delays of the rhythms depending on the timing of treatments, and the shifts are completely blocked by the GC receptor antagonist, mifepristone. The DEX-induced phase-response curve differs from that induced by the vehicle. The fetal SCN is sensitive to GCs in vivo because DEX administration to pregnant rats acutely downregulates c-fos expression specifically in the laser-dissected fetal SCN. Our results provide evidence that the rodent fetal SCN clock may respond to changes in GC levels.
Keywords: Hypothalamus; dexamethason; Pregnancy; ontogenesis; hypothalamus; circadian clock; Glucocorticoids; mPer2 mouse; Placenta; entrainment; Female; suprachiasmatic nuclei; krysa rodu Rattus; zvířata; myši; vývoj plodu; Mice; Fetus; plod; Circadian Clocks; ženské pohlaví; nucleus suprachiasmaticus; Male; Dexamethasone; glukokortikoidy; těhotenství; Fetal Development; Rats; cirkadiánní hodiny; glucocorticoids; Animals; mužské pohlaví; placenta; cirkadiánní proteiny Period; Suprachiasmatic Nucleus; Period Circadian Proteins